Work-life balance by area, actual situation and expectations - Kozjek, Tatjana (Organizacija (Kranj), 2014)
Background: The question of work-life balance (WLB) is an area where increasing attention is being paid nowadays. States, organisations and employees all have responsibility and a role to play in WLB. This article presents the important areas of the WLB by key players in this field. Purpose:The purpose of the research was to compare and analyse the differences between the actual situation and the expectations of employers and employees with regard to specific areas of WLB in Slovenia. Methodology: Data was gathered using the Computer Assisted Web Interview (CAWI) method. In the first part of the research project, employers across all sectors of the economy in Slovenia were questioned and in second part focussed on employees. In order to verify the areas in which employers and employees agree and those in which there are differences in perception, multidimensional scaling (MDS) was used. Results: The results of our research show that Slovenian organisations must pay more attention to flexible working time, the employees' ability to take time off to care for family members, time and stress management workshops and paid leave for parents on a child's first day of school. Conclusion: A significant role in WLB is played by organisations. The incorporation of WLB strategies into the strategic and financial planning of an organisation can, in fact, have positive business, economic and social effects. Employees have to express their expectations and needs, which is the only way that employers can be made aware of their problems and help with WLB. State responsibility is to encourage all social partners to shape the living environment in which employees' can achieve a good WLB with an emphasison gender equality.
Keywords: delo; labour; družina; family; privacy; zasebnost; zaposleni; delodajalci; kvaliteta življenja; Slovenia; Slovenija